Comparison of 18‐ and 22‐MHz probes for the ultrasonographic diagnosis of giant cell arteritis. Issue 6 (10th February 2021) - Noumegni, Steve Raoul; Hoffmann, Clément; Jousse‐Joulin, Sandrine; Cornec, Divi; Quentel, Hugo; Devauchelle‐Pensec, Valérie; Saraux, Alain; Bressollette, Luc
Abstract: Purpose: Little is known about the diagnostic concordance of images provided by ultrasound probes with emitting frequencies below or above 20 MHz for the diagnosis of giant cell arteritis (GCA). Methods: We compared, using Cohen's kappa statistic, data obtained with an 18‐MHz and a 22‐MHz probe for the ultrasonographic evaluation of temporal arteries in 80 patients referred for suspected GCA. Results: The halo sign was found in 25% of cases with the 18‐MHz probe and in 35% with the 22‐MHz probe. The compression sign was positive in 42% of cases with the 18‐MHz probe and 48% with the 22‐MHz probe. GCA was finally diagnosed in 20 patients (25%). The kappa coefficient of agreement was 0.76 ( P < .001) for the halo sign, and 0.75 ( P < .001) for the compression sign. Conclusions: Images obtained by 18 MHz and 22‐MHz frequency probes showed a good level of agreement for the diagnosis of GCA, but the 22‐MHz probe yielded a correct diagnosis of GCA in 3 of the 7 patients in whom examination with the 18‐MHz probe was negative.